Can acute stress be fatal? A systematic cross-disciplinary review. (4th May 2019) - Baltzer Nielsen, Solveig; Stanislaus, Sharleny; Saunamäki, Kari; Grøndahl, Carsten; Banner, Jytte; Jørgensen, Martin Balslev
Abstract: In this review it is discussed if acute stress can be fatal. The review is based on literature searches on PubMed, PsycINFO as well as Web of Science. Literature concerning the conditions excited delirium syndrome (ExDS), malignant catatonia, takotsubo cardiomyopathy (TCM), and capture myopathy (CM) is reviewed and compared. The aim of the article is to identify and discuss a possible fatalness as well as a common pathophysiology behind these conditions. This includes a deregulated autonomic nervous system, neurocardiac reasons for myocardial damage, and rhabdomyolysis. We conclude that these conditions could be different manifestations of the same pathophysiological phenomenon. In addition, we suggest that it is possible to die from acute stress, but that it requires a prior sensitization, as seen in cocaine abusers and certain psychiatric patients, to render individuals disposed to an extreme autonomic nerve reaction. Lay summary This article compares different conditions in humans and in other animals, where it appears as if the human or animal dies with no other reason than being submitted to an extreme condition of mental stress. The conditions examined via a literature search are excited delirium syndrome, malignant catatonia and takotsubo cardiomyopathy in humans, and a capture myopathy in different mammals. The article theoretically suggests that one can die solely from acute stress, but that different forms sensitization probably goes ahead of such a fatal stress reaction. E.g. in cocaine addicts, some psychiatric patients, and in wild animals formerly subjected to stress an extreme sympathetic stress response might be immediately fatal. The article also theorizes that excited delirium syndrome, malignant catatonia, and capture myopathy could be more severe and acute variants of the temporary condition seen in takotsubo patients, also known as patients with broken heart syndrome.